Association between maternal infections during pregnancy and congenital defects in their offspring: a population-based case-control study in Bogota and Cali, Colombia 2001–2018. (12th December 2022) - Rumbo, Jose; Madariaga-P, Ithzayana; Salazar-Reviakina, Alexander; Sierra-Breton, Maria; Tovar, Catherin; Sequera, Diana; Rodríguez, Catherin; Holguín, Jorge; Hurtado-Villa, Paula; Sarmiento, Karen; Zarante, Ignacio
Abstract: Infections are frequent during pregnancy and their teratogenic role is well documented in Toxoplasmosis, other infections, Rubella, Cytomegalovirus, and Herpes simplex (TORCH). However, the in-utero development effects of the rest of the infections that affect pregnant women are unknown. We described a cohort of patients with major Birth Defects (BD) and the exposure to infections during pregnancy from the information of Congenital Defects Surveillance Programs of two Colombian cities (Bogota and Cali) between 2001 and 2018. We evaluated associations between groups of maternal infections and BD among 3096 cases and 7446 controls that were registered. BD presentation was more frequent as isolated (64.3%), polymalformed (23.2%), and syndromic (12.4%). Infections during pregnancy were present in 52.5% of cases and 44.6% of controls. The most common single infection between cases and controls was vaginal infection. The most common polyinfection was vaginal and urinary tract infection. We found an association between BD and vaginal infections with an odds ratio (OR) 1.18 (CI 1.08–1.30), urinary tract infections OR 1.16 (CI 1.05–1.28), gastrointestinal infections OR 2.06 (IC 1.18–3.59), respiratory infections OR 1.56 (IC 1.28–1.9) and viral infections OR 1.88 (IC 1.18–3.0). Knowing the teratogenic effect of infections is important to extend prevention, screening, timely diagnosis, and appropriate treatment to pregnant women.